Live Faecalibacterium prausnitzii in an apical anaerobic model of the intestinal epithelial barrier. (31st October 2014) - Ulluwishewa, Dulantha; Anderson, Rachel C.; Young, Wayne; McNabb, Warren C.; van Baarlen, Peter; Moughan, Paul J.; Wells, Jerry M.; Roy, Nicole C.
Summary F aecalibacterium prausnitzii, an abundant member of the human commensal microbiota, has been proposed to have a protective role in the intestine. However, it is an obligate anaerobe, difficult to co‐culture in viable form with oxygen‐requiring intestinal cells. To overcome this limitation, a unique apical anaerobic model of the intestinal barrier, which enabled co‐culture of live obligate anaerobes with the human intestinal cell line Caco‐2, was developed. Caco‐2 cells remained viable and maintained an intact barrier for at least 12 h, consistent with gene expression data, which suggested Caco‐2 cells had adapted to survive in an oxygen‐reduced atmosphere. Live F. prausnitzii cells, but not ultraviolet (UV)‐killed F. prausnitzii, increased the permeability of mannitol across the epithelial barrier. Gene expression analysis showed inflammatory mediators to be expressed at lower amounts in Caco‐2 cells exposed to live F. prausnitzii than UV‐killed F. prausnitzii, This, consistent with previous reports, implies that live F. prausnitzii produces an anti‐inflammatory compound in the culture supernatant, demonstrating the value of a physiologically relevant co‐culture system that allows obligate anaerobic bacteria to remain viable.